2013
DOI: 10.1680/stbu.12.00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybrid fibre reinforcement on capacity of reinforced concrete beams

Abstract: This study evaluates the flexural behaviour of reinforced concrete beams strengthened by hybrid fibre reinforcement.Hybrid fibre reinforcement prepared in two ways is considered: using a hybrid fibre sheet and a hybrid fibre plate.Experimental research on the feasibility and applicability of strengthening effects due to hybrid fibre plate and hybrid fibre sheet in reinforced concrete beams has been carried out. Each of control and seven specimens strengthened by hybrid fibre sheet and hybrid fibre plate was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Besides that, other study evaluated the strengthening method using fibre reinforcement on RC beams [13]. The study found that the flexural behavior of beams strengthened with hybrid fibre reinforcement (sheet or plate) was 60% -200% higher for its reinforcing effect than the non-reinforced beams.…”
Section: Related Previous Studymentioning
confidence: 99%
“…Besides that, other study evaluated the strengthening method using fibre reinforcement on RC beams [13]. The study found that the flexural behavior of beams strengthened with hybrid fibre reinforcement (sheet or plate) was 60% -200% higher for its reinforcing effect than the non-reinforced beams.…”
Section: Related Previous Studymentioning
confidence: 99%
“…[4][5][6] In addition, the formation of small cracks in concrete members reinforced by untreated bamboos starts after shrinkage of bamboos and results in low strength of the entire reinforcement. [7][8][9] Furthermore, the interfacial bond initiation between concrete and bamboo candidate is another important parameter of the process. It is well known that the putative industrial material, the steel bar is very expensive due to its manufacturing process as well as its related raw materials which are ultimately scarce.…”
Section: Introductionmentioning
confidence: 99%